(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2017)
Many attempts have been made at the unification of General Relativity (GR) and Quantum Theory (QT), but there is a fundamental error made with these attempts, as we will discuss. What is the point of such theories? Well, obviously to describe the physical world we live in. QT describes what happens on the tiny scale, and GR describes what happens to bodies on a large scale. The fundamental error in unifying the two subjects is that QT doesnâ€™t provide the physical happenings for GR to work, or in other words, QT describes why the world is the way it is, but not how, and this does not philosophically suffice in GR. Must we simply give up, in that the subjects are two different entities? I think the answer is that we mustn’t. I think that we should put one theory in terms of the basic mechanics of the other, perhaps by simplifying, or perhaps by taking the physical reality to be our guide. Do I believe QT describes the world? Accurately. Do I believe that QT is the physical truth? Of course notâ€¦ it is simply a mathematical construct to provide a model that allows for us to predict future outcomes. I will begin very simplistic, but the goal for the first part of the paper is to Classically describe the physical mechanics of QT. I will stick with particles in their ground state, and hence no translational motion.